Changing maternal and child nutrition practices through integrating social and behavior change interventions in community-based self-help and support groups: literature review from Bangladesh, India, and Vietnam - Verma, Anumeha; Nguyen, Tuan; Purty, Appolenarius; Pradhan, Narottam; Husan, Alomgir; Zambrano, Paul; Mahmud, Zeba; Ghosh, Sebanti; Mathisen, Roger; Forissier, Thomas (Frontiers in Nutrition, 2024)
Introduction: Self-help groups (SHGs) and Support Groups (SGs) are increasingly recognized as effective mechanisms for improving maternal and young child nutrition due to their decentralized, community-based structures. While numerous studies have evaluated the outcomes and impact of SHGs and SGs on nutrition practices, there remains a gap in the literature. To address this, we conducted a literature review to examine the role of SHGs and SGs in improving health and nutrition outcomes, focusing on marginalized women, especially pregnant and lactating women (PLW), in India, Bangladesh, and Vietnam, with an emphasis on programs supported by the international non-governmental initiative, Alive & Thrive.We conducted a literature review to assess various models, summarizing findings from 34 documents, including research studies, evaluation reports, program materials, strategies, annual reports, work plans, and toolkits. Relevant information from these documents was extracted using predetermined forms.In India, the models used SHGs with 10-20 women, federated into larger village and district organizations. Bangladesh and Vietnam have similar structures but with local leaders and committees playing key roles. In all three countries, interventions aimed to improve health and nutrition practices through social behavior change (SBC) interventions, including peer-to-peer learning, interpersonal communication, home visits, and community meetings.Outcomes of the interventions showed that SHG members had increased knowledge of breastfeeding, complementary feeding, and improved dietary diversity compared to non-SHG participants. Interventions helped improve infant and young child feeding practices. Common challenges included sustaining the SHGs, ensuring adequate participation, socio-cultural barriers, and logistical difficulties in reaching PLW in remote areas. Limited time for health topics during SHG meetings and the dissolution of older SHGs were also significant issues.: SHG-based models demonstrate success in improving health and nutrition outcomes but face challenges in scale, sustainability, and participation. Integrating nutritionfocused SBC interventions into SHGs and SGs requires significant capacity building for technical and counseling skills. Ensuring comprehensive coverage and robust quality assessment during community-based rollouts is essential. To sustain these interventions, it is crucial to prevent group dissolution, allow time for maturation, and secure strong stakeholder engagement and political support.